Effects of inoculants on the quality of alfalfa silage - Wang, Si-Yi; Jing, Yuan-Yuan; Yang, Guolin; Liu, Bin; Gao, Feng-Qin (Frontiers in Microbiology, 2025)
To explore the effects of different silage inoculants on the silage quality of alfalfa (Medicago sativa L.), the experiment used Alfalfa with a moisture content of 60.00% after harvesting as the raw material. The treatments included a control group containing only distilled water (CK), Xinlaiwang I-straw silage agent (A), Xinlaiwang I-alfalfa silage agent (B), Zhuanglemei silage fermentation agent (C), Baoshiqing (D), and Kangfuqing S lactic acid bacteria inoculant (E), totaling six treatments. After 60 days of normal temperature sealing treatment, the silage fermentation and nutritional indicators of Alfalfa were measured, and the silage fermentation effect was analyzed by the membership function method. The experiment showed that when the moisture content of alfalfa was 60.00%, the neutral detergent fiber (NDF) and acid detergent fiber (ADF) contents of the silage agent treatment groups were significantly lower than those of the CK group (p < 0.05). The lactic acid (LA) content was significantly higher in the treatment group than in the CK group (p < 0.05). The addition of Xinlaiwang I-alfalfa silage agent in group B significantly increased the crude protein (CP) and LA levels in the Alfalfa silage (p < 0.05). It also reduced the neutral detergent fiber (NDF) and acid detergent fiber (ADF) contents. Additionally, the pH and Ammonia Nitrogen/Total Nitrogen (AN/TN) ratio were lowered. Propionic acid (PA) and butyric acid (BA) were not detected. After the membership function calculation, the average membership value of Xinlaiwang I-alfalfa silage agent (B) group was the highest with a score of 0.90, ranking first, and the silage quality was the best. In summary, through quality analysis and membership function calculation, Xinlaiwang I-alfalfa silage agent can effectively improve the silage quality of WL298HQ alfalfa.